Map of the family social support network for the promotion of child development - Alexandre, Ana Maria Cosvoski; Labronici, Liliana Maria; Maftum, Mariluci Alves; Mazza, Verônica de Azevedo (Revista da Escola de Enfermagem da USP, 2012)
This descriptive, qualitative study was performed from September to November 2009, at a Family Health Strategy unit in a city in the metropolitan region of Curitiba-PR. Participants were eight families, represented by mothers, fathers and grandmothers. The study objective was to identify the family social support network for the promotion of child development, from the family's perspective. Data were collected through focal groups and subjected to content analysis. The family social support network was classified as located, consisting of 16 members distributed between the informal and formal network, established by close relationships, with a smaller level of commitment, and occasional. It is considered that the health workers' understanding regarding the role and importance of this network favors the networking proposal between members that contribute to supporting families in the promotion of child development.